Bi-/multilingualism and the perceptions of the gender of objects - Chłopek, Zofia (Glottodidactica, 2010)
The newest research confirms the ‘weak’ version of the linguistic relativity hypothesis, according to which the language we speak influences to some extent the way we think. At the same time, it has been shown that the conceptual representations of reality which have been shaped by the mother tongue from birth play a significant role while using an L2 (L3 etc.), especially when it is weaker than the L1. The present article describes one such conceptual domain – the (non-linguistic) categorization of objects according to their perceived gender, which is influenced by the grammatical gender of their names.